Why N,N-dimethyltryptamine matters: unique features and therapeutic potential beyond classical psychedelics - Chaves, Cristiano; dos Santos, Rafael G.; Dursun, Serdar M.; Tusconi, Massimo; Carta, Mauro Giovanni; Brietzke, Elisa; Hallak, Jaime E. C. (Frontiers in Psychiatry, 2024)
Graphical Abstract